Pengaruh Transparansi Terhadap Perkara Koperasi Simpan Pinjam Indosurya - Fathya Kamila; Muhammad Rizal; Tetty Herawati; Dodi Sukmayana (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
Cooperatives are business entities that are formed from individuals and legal entities that are carried out on the principles of cooperatives based on the principle of kinship. Transparency will make it easier for interested parties in assessing and evaluating the performance of cooperatives. Accountability will improve the performance of cooperatives because the various work results made can be answered well. Independence will make the company more objective in making decisions. In this study it was found that the performance of cooperatives in Indosurya experienced a lot of incompleteness due to existing cases. In the national economic governance compiled as a joint effort based on the principle of family and economic democracy. Transparency will make it easier for interested parties in assessing and evaluating the performance of cooperatives. Accountability will improve the performance of cooperatives because the various work results made can be answered well. Responsibility in which a company is able to carry out company activities in accordance with applicable rules. Independence will make the company more objective in making decisions.